Some conditions for finiteness and commutativity of rings - Howard E. Bell; Franco Guerriero (International Journal of Mathematics and Mathematical Sciences)
We present several new sufficient conditions for a ring to be finite; we give two conditions which for periodic rings R imply that R must be either finite or commutative; and we study commutativity in rings with only finitely many non-central subrings.